Governing Death: Organizing End-of-life Situations. Issue 4 (April 2020) - Le Theule, Marie-Astrid; Lambert, Caroline; Morales, Jérémy
This paper examines the organization of death. Through an ethnographic study, we examine how a geriatrics department guides the end of life. Drawing on Agamben, we show that organizations that are dedicated to life, but regularly confronted with death, develop dispositifs (mechanisms, technologies, practices and relationships) to turn biopolitics (power over life) into thanatopolitics (a regime of death). We also show how the inherently political meaning of life disrupts such government of death. The inclusion of political life in a regime of death disrupts organizational practices that find themselves facing fundamental questions of what makes a life worth living, who can decide not to prolong life, and based on which criteria.